PERANCANGAN PUSAT PENELITIAN DAN PENGEMBANGAN TANAMAN HUTAN TROPIS BERBASIS EDUKASI DI KOTA BOGOR - Hernawati Hernawati; Atie Ernawati; Ryan Hidayat (Lakar: Jurnal Arsitektur, 2021)
Bogor City has a forest area of 282.58 ha which is identified as urban forest. Around 2.3% of the land in Bogor City is planted with forest plantations. The existence of a fairly large forest in the city of Bogor, requires more attention in the maintenance and development of the forest. One of the efforts to maintain and develop forests in Bogor City is to facilitate research and development of forest plants themselves. In addition to research activities, buildings must also be able to support educational activities for the community so that all levels of society can be educated in maintaining and protecting forests. Therefore, to support educational activities about forest plants, an education-based Tropical Forest Plant Research and Development Center will be designed in Bogor City.